2023
DOI: 10.3390/cimb45030122
|View full text |Cite
|
Sign up to set email alerts
|

Ductal Hyperkeratinization and Acinar Renewal Abnormality: New Concepts on Pathogenesis of Meibomian Gland Dysfunction

Abstract: Meibomian gland dysfunction (MGD) is a functional and morphological disorder of the meibomian glands which results in qualitative or quantitative alteration in meibum secretion and is the major cause of evaporative dry eye (EDE). EDE is often characterized by tear film instability, increased evaporation, hyperosmolarity, inflammation, and ocular surface disorder. The precise pathogenesis of MGD remains elusive. It has been widely considered that MGD develops as a result of ductal epithelial hyperkeratinization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 88 publications
(152 reference statements)
0
3
0
Order By: Relevance
“…Hyperkeratinization 81 of the excretory duct seems to be the initial pathological step in obstructive MGD with PMN infiltration playing a particularly important pathogenic role. 54 , 55 Previous studies reported that the lung overloaded with UPM led to keratinization, and lung protein cysts, as well as promoted neutrophil infiltration by triggering the inflammation response.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperkeratinization 81 of the excretory duct seems to be the initial pathological step in obstructive MGD with PMN infiltration playing a particularly important pathogenic role. 54 , 55 Previous studies reported that the lung overloaded with UPM led to keratinization, and lung protein cysts, as well as promoted neutrophil infiltration by triggering the inflammation response.…”
Section: Discussionmentioning
confidence: 99%
“…AZR-MD-001 is a topical medication containing selenium sulfide and is believed to be an agent with keratostatic properties that reduce keratin synthesis by slowing keratinocyte proliferation and turnover, preventing hyperkeratinization of the MG ducts, as well as keratolytic properties that promote the effective release of blockages [ 76 ]. As mentioned earlier, MGD has various etiologies, including structural abnormalities of MG secondary to aging that can lead to evaporative DED [ 65 , 77 ]. Concordantly, a negative correlation with age was found in the mean length of the upper ( r = −0.485, p < 0.05) and lower MG ( r = −0.533, p < 0.001), as well as in the percentage area of MG acini of the upper ( r = −0.592, p < 0.05) and lower MG ( r = −0.357, p < 0.05) [ 78 ].…”
Section: Dry Eye Disease Sourcesmentioning
confidence: 99%
“…45 This process has also been termed hyperkeratinization. 46 As a result, recent investigations have demonstrated that the modification of keratin pathways may offer novel mechanistic treatments, spawning the development of keratolytic medications. 47 Selenium sulphide ointment (AZR-MD-001; Azura Ophthalmics Ltd, Tel Aviv, Israel) is the first brand of keratolytic agents for treating lid margin diseases and associated conditions.…”
Section: Selenium Sulphide Ointmentmentioning
confidence: 99%